Status quo and problem analysis of cervical cancer screening program in China: Based on RE-AIM framework - Zhu, Jingfen; Ge, Zhenghao; Xia, Jiawei; Liu, Qi; Ran, Qingqing; Yang, Yongbin (Frontiers in Public Health, 2022)
Background An organized cervical cancer screening program is an effective method to prevent and control cervical cancer. This study aims to find barriers and facilitators in the implementation process of National Cervical Cancer Screening Program in Rural Areas (NACCSPRA) in China through program evaluation, and thus propose suggestions for optimization of the program. Methods Through stratified sampling, 8 provinces (autonomous cities/districts) in eastern, southern, western, northern, and central China were selected for evaluation of NACCSPRA based on the RE-AIM framework. We obtained 15 program providers' experience and perspectives through semi-structured interviews. The data was analyzed using a combination of deductive and inductive analysis methods. Results The study found that NACCSPRA mainly serves women with rural household registration or urban minimum living guarantee. Population mobility and certain demographic characteristics such as low education and poor health awareness are common participation barriers, while program publicity acts as a facilitator. A screening program's direct benefit is to promote early detection and treatment of cervical cancer, and its perceived indirect effect is to raise people's health awareness. The proportion of regions adopting the project is relatively high, and factors affecting employees' participation are screening workload, working environment, welfare benefits, degree of preference for grassroots work, and whether the project is included in the performance appraisal; In terms of implementation, there are disparities in screening methods, network informatization levels, and capital investment in various regions. Poor development of screening information system and insufficient screening funds are significant barriers to improvement of project implementation. In contrast, the overall implementation of follow-up is better; related policies issued by the local government and financial subsidies for poor women ensure the maintenance of the project. Conclusion Shortage of funds is an important problem faced by current screening project, which negatively influences upgrade of cervical cancer prevention strategy, implementors' working environment, and impedes improvement of information network. In addition, defects in population coverage, especially in mobile population also deserves attention. The study found barriers and facilitators of NACCSPRA perceived by project providers and provided a theoretical foundation for project optimization.